2011
DOI: 10.1111/j.1439-0329.2009.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Cedrus libani: the most susceptible Turkish conifer species to local Heterobasidion isolates in spring inoculations

Abstract: Five-year-old seedlings of Pinus nigra, Pinus brutia, Abies nordmanniana ssp. bornmü lleriana and Cedrus libani, 3-year-old seedlings of Pinus sylvestris, and 2-year-old seedlings of Juniperus excelsa were inoculated on the lower stem with Turkish Heterobasidion abietinum and Heterobasidion annosum s.s. isolates. In total, 300 seedlings were inoculated in April 2007 with five isolates of each Heterobasidion species and incubated in a glasshouse for 12 weeks. The daily maximum temperature increased gradually fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 27 publications
7
19
1
Order By: Relevance
“…However, there was no difference in the mortality rate of the infected and control seedlings treated by soil infestation. Nevertheless, rates were similar to or even higher than observed by other authors (Lehtijarvi et al 2011;Scire et al 2011), who reported low mortality rates in other pine species, such as P. pinea, P. halepensis, P. nigra, P. sylvestris and P. brutia seedlings. The mortality rates (approximately 35 and 10% for stem inoculation and soil infestation, respectively) were lower than reported for some North American pine species, such as P. elliottii, P. echinata, P. palustris, P. strobus and P. taeda (Delatour et al 1998), and, to a lesser extent, for P. sylvestris (Swedjemark and Stenlid 1995), although inoculation methods were different from those used in this study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, there was no difference in the mortality rate of the infected and control seedlings treated by soil infestation. Nevertheless, rates were similar to or even higher than observed by other authors (Lehtijarvi et al 2011;Scire et al 2011), who reported low mortality rates in other pine species, such as P. pinea, P. halepensis, P. nigra, P. sylvestris and P. brutia seedlings. The mortality rates (approximately 35 and 10% for stem inoculation and soil infestation, respectively) were lower than reported for some North American pine species, such as P. elliottii, P. echinata, P. palustris, P. strobus and P. taeda (Delatour et al 1998), and, to a lesser extent, for P. sylvestris (Swedjemark and Stenlid 1995), although inoculation methods were different from those used in this study.…”
Section: Resultssupporting
confidence: 90%
“…1a). However, the lesion lengths were substantially higher than those observed in other pine species in Turkey, such as P. brutia (9.4 mm), P. nigra (15.7 mm) and P. sylvestris (15 mm) (Lehtijarvi et al 2011). The lesion lengths in stem inoculations were consistent with other findings in Picea abies (Swedjemark et al 2001), where an average lesion length of approximately 50 mm 182 days was found after inoculation.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Holmboe and P. sylvestris L. Based on inoculation experiments, however, C. libani appears the most susceptible native species to Turkish isolates of Heterobasidion (Lehtijärvi et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Bref. (Lehtijärvi et al, 2011) and Sphaeropsis sapinea (Fr.) Dyko et Sutton (Doğmuş- Lehtijärvi et al, 2009) in mycelial inoculations -without being their natural host.…”
Section: Discussionmentioning
confidence: 99%